Clasificación ecológica y caracterización selvícola y PRODUCTIVA DEL PARQUE NATURAL DE LOS ALCORNOCALES (CÁDIZ y MÁLAGA) - Torres Álvarez, E; Montero González, G; V ÁZQUEZ PIQUÉ, F J (II Congreso Forestal Español, 1997)
An ecological classification of the Natural Park "Los Alcornocales" (Cádiz and Málaga, Spain) and a silvicultural and productive characterisation are done. The territorial c1assification is assisted by a Geographical Information System. Sixteen Territorial Classes and five classes of cork-oak potentiality are defined and mapped. Using a sample of seventy two plots, the cork-oak forests of this area are silvicultural and productively characterised, according their Territorial Class.
Keywords: Cork; cork-oak; Ecological classification; Geographical inforn1ation system; Potentiali ty; Quercus suber